Financial security for dummies - Tyson, Eric (For Dummies, 2021)
Boost your financial health so you're ready for any economic or personal upheaval Crisis is inevitable--but it doesn't have to torpedo your finances! Financial Security For Dummies offers proven advice to help you prep your finances for the next economic downturn, personal setback, pandemic, plague of locusts--or anything else life throws your way. This book contains the historical perspective and up-to-date info you'll need to anticipate, understand, and navigate a wide range of personal financial challenges. If your monthly income and expenses are on steady ground and you're ready to secure your financial future, this is the For Dummies guide for you. Not only will you create a plan to keep your family's finances afloat during turbulent times, but you'll also be liberated from the pressure to "keep up with the Joneses" so you can make smarter financial decisions, starting today. This book will help you: Gain an understanding of how unforeseen personal or global events could affect your financial life Learn strategies for protecting your assets when economic downturns and other emergencies occur Feel confident in your unique path to financial freedom so you can remain calm when life takes an unexpected turn Build a survival plan for protecting yourself with broader safety nets, better money decisions, and improved financial literacy Whether you want to reduce your stress surrounding your financial goals or take advantage of financial opportunities crises create, Financial Security For Dummies will equip you to navigate financial challenges and ultimately achieve peace of mind.
Description based on CIP data; resource not viewed
Keywords: Finance, Personal